2013
DOI: 10.3182/20130703-3-fr-4038.00155
|View full text |Cite
|
Sign up to set email alerts
|

What can regularization offer for estimation of dynamical systems?

Abstract: Estimation of unknown dynamics is what system identification is about and a core problem in adaptive control and adaptive signal processing. It has long been known that regularization can be quite beneficial for general inverse problems of which system identification is an example. But only recently, partly under the influence of machine learning, the use of well tuned regularization for estimating linear dynamical systems has been investigated more seriously. In this presentation we review these new results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Regularized regression, like LASSO, is used to prevent overfitting and perform feature selection in computational statistics and machine learning (e.g., Imangaliyev et al, 2018 ). Regularization for estimating models of dynamical systems has been investigated in much lesser extent (Chen, 2013 ). We and others have shown that regularization can be very effective to mitigate ill-conditioning when estimating dynamic systems biology models (van Riel et al, 2013 ; Gábor and Banga, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regularized regression, like LASSO, is used to prevent overfitting and perform feature selection in computational statistics and machine learning (e.g., Imangaliyev et al, 2018 ). Regularization for estimating models of dynamical systems has been investigated in much lesser extent (Chen, 2013 ). We and others have shown that regularization can be very effective to mitigate ill-conditioning when estimating dynamic systems biology models (van Riel et al, 2013 ; Gábor and Banga, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Minimizing the cost function, V N (θ, Z N ), involves a trade-off between bias and variance that is determined by the selection of model order. Regularization constants Λ and R are determined to reduce the variance of the model estimates, and the regularized ARX model is solved; i.e. where θ* is the mean of the prior distribution of θ which is assumed to be Gaussian …”
Section: Methodsmentioning
confidence: 99%
“…where θ* is the mean of the prior distribution of θ which is assumed to be Gaussian. 41 Since the PM algorithm uses small amounts of routine operating data, the signal-to-noise ratio is improved by filtering out high frequency noise. This denoising step is performed after the IO data is filtered with the inverse noise model estimate.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…Optimal values should minimize the cost function, which is a mean square error, given by a sum of systematic error (bias) and random error (variance). This penalty function is thus a tradeoff in creating the model [14]. Therefore, optimal set of parameters (θ opt ) in vectorized format is obtained from:…”
Section: Model Structurementioning
confidence: 99%